Gentamicin-loaded ceramic-biopolymer dual layer coatings on the Ti with improved bioactive and corrosion resistance properties for orthopedic applications. (June 2018) - Mohan Raj, R.; Priya, P.; Raj, V.
Abstract: In orthopedic surgery, osteomyelitis (bone infection) is one of the most serious complications in the last few decades and the resident drug delivery is the key strategy to overcome this issue. Combination of bioactive materials with antibiotics is broadly developed for the handling of osteomyelitis which plays a dual role as bone cell growth and as local drug delivery systems for antibiotic delivery. TiO2 -SiO2 mixtures were fabricated on Ti alloy by anodization method. Chitosan-Lysine (CS-LY) biopolymers were coated on composites by electrodeposition method and followed by gentamicin sulfate (GS) which was loaded as a model drug. The layers were characterized by AT-FTIR, XRD, FE-SEM and EDX methods. The mechanical, anticorrosion, antimicrobial effects and biocompatibility of the glazes were considered. In addition, drug loading, continued and prolonged liberation behaviors of GS from the fabricated coating were studied. The apatite development ability and cell viability are outstanding for CS-LY-3 coated composites. In vitro cell experimentations indicate that osteoblasts show good adhesion and high growth rates for CS-LY-3 coated TiO2 -SiO2 composite substrate. In conclusion, the surface modification of TiO2 -SiO2 /CS-LY-3 coated Ti alloy could be used as a carrier for GS, not only to eradicate the osteomyelitis caused by Gram-negative and Gram-positive bacteria, but also to repair the bone defect initiated by the infection owing to the tunable nanocomposite degradation. Graphical abstract: fx1